POLITICAL DISCOURSE IN COMEDIES OF BRANISLAV NUŠIĆ - Stanojevic, Dobrivoje (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
The comedic discourse is a very important hub where the elements of the political discourse are refracted, often in an ironic-satirical formulation. For our conditions, it is particularly important to examine the contextualization of political discourse in Branislav Nušić's comedies. There is hardly any of his work that does not represent aspects or a hidden view of political discourse. This imposes a broader interdisciplinary approach, among the first a structural approach, the interpretation of the represented macro and microstructures of comedy in which a narrative diversionary action is performed through political discourse. Hence, the conditional stylistic-rhetorical, intertextual and linguistic approach should be supplemented with elements of discourse analysis. This will enable an insight into the structural design of the comedy. Parts of microstructures from other contexts (social, political, ideological, literary, everyday) often have multiple parallel roles. One is the delineation and criticism of social reality, the other is the shaping of the fictitious world of comedy with important literary premises. Changing the context of certain microstructures conditions different behavior and interpretation, as well as significant humorous motivation.
Keywords: political discourse, comic, satire, parody, irony, caricature, grotesque, dystopia